ANALISIS POLA PEMBELIAN KONSUMEN DI PT XYZ MENGGUNAKAN MARKET BASKET ANALYSIS - Dio Putra; Jito Armando; Aldi Mulia; Aulia Agung Dermawan (Fakultas Rekayasa dan Teknologi Industri, 2026)
Market Basket Analysis (MBA) is a data mining approach used to identify association patterns between products in transaction data. This approach is useful for retail companies in understanding consumer purchasing behavior and designing targeted marketing strategies. This study aims to analyze consumer purchasing patterns at PT XYZ, a household and snack retail company, using the FP-Growth algorithm. The data consists of 1,200 customer transactions from January to March 2025. The FP-Growth algorithm was applied with a minimum support of 5% and a confidence level of 60%. The analysis results show product combinations with strong associations, such as